USING ROBOT OPERATING SYSTEM FOR AUTONOMOUS CONTROL OF ROBOTS IN EUROBOT, ERC AND ROBOTOUR COMPETITIONS - Grzegorz Granosik; Kacper Andrzejczak; Mateusz Kujawinski; Rafal Bonecki; Lukasz Chlebowicz; Blazej Krysztofiak; Konrad Mirecki; Marek Gawryszewski (Acta Polytechnica CTU Proceedings, 2016)
This paper presents application of the Navigation Stack available in Robot Operating System as a basis for the autonomous control of the mobile robots developed for a few different robot competitions. We present three case studies.